2010
DOI: 10.2967/jnumed.109.072298
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Acute and Chronic Aortic Dissection by 18F-FDG PET/CT

Abstract: By conventional imaging modalities, the discrimination between acute and chronic aortic dissection (AD) for surgical risk evaluation is not possible. However, acute and chronic stable AD potentially may be distinguished by detection of reparatory hypermetabolism in the lacerated aortic wall of acute AD using 18 F-FDG PET/CT. In this study, we analyzed the 18 F-FDG uptake in the aortic wall of acute and chronic stable AD. Methods: Eighteen patients with acute (n 5 9), symptomatic progressive (n 5 2), or known c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…1). We finally found 22 eligible articles11121314151617181920212223242526272829303132. Most studies were from Asian and European countries (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). We finally found 22 eligible articles11121314151617181920212223242526272829303132. Most studies were from Asian and European countries (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…During the last 10 years, an increasing number of case-control and observational studies have reported the diagnostic accuracy of D-dimer for AAD11121314151617181920212223242526272829303132. In addition, a few systematic reviews and meta-analyses have calculated the pooled sensitivity and specificity using a univariate fixed- or random-model567891027.…”
mentioning
confidence: 99%
“…Inflammation plays a role in the pathophysiology of the disease [87,88]. In patients presenting with acute aortic syndrome who underwent acute FDG-PET imaging, there was a trend to less progression of disease in those with lower degrees of FDG uptake [89]. A study by Kato et al [90]., in subjects with both acute and chronic dissection, suggested worse outcomes in those with the highest aortic FDG uptake at the point of maximal dilatation.…”
Section: The Potential Of Fdg-pet Imaging In Aortic Aneurysm and Aortmentioning
confidence: 99%
“…IVUS has similarly been reported to have www.frontiersin.org both high sensitivity and specificity, however, is similarly compromised by its invasiveness (2,29). The use of positron emission tomography (PET) has also been reported; in the acute setting areas of elevated metabolic activity at freshly disrupted segments of aortic wall show increased uptake of radionuclide tracer (12). In asymptomatic patients with chronic aortic dissection, however, no noticeable uptake is detected, hindering its use as a prognostic indicator in this setting (12).…”
Section: Other Imaging Modalitiesmentioning
confidence: 99%
“…For type B dissection patients who have been medically managed, a persisting FL in the chronic phase correlates with an increased risk of aortic enlargement (11). Hence, regardless of the initial management in aortic dissection, careful follow-up with appropriate imaging is mandated (12). Several international guidelines recommend the close follow-up of these patients; however multiple imaging modalities are currently used without a clear consensus of the gold standard (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%